Pemanfaatan Lumpur Minyak untuk Pembuatan Komposit Berserat Lignoselulosa Utilization of Oil Sludge as a Lignocellulosic Fiber Reinforced Composite Material - Bambang Prasetya; Sudijono Sudijono; Purwadi Kasinoputro (Jurnal Ilmu dan Teknologi Kayu Tropis, 2006)
Utilization of Oil Sludge (OS) is facing until now many problems due to heavy metal content. This experiment tried to find out an alternative how to use of OS as a lignocellulosic fiber reinforced composite material. One important reason for this purpose is the wide utilization of composite material for building material. Two problems have to be solved are how to catch the heavy metal and how to increase the bonding ability of OS. In this experiment additive PTA08 was used for catching the heavy metal. The OS with additive PTA were mixed at temperature of 80ºC and fiber in varying composition (40, 50 and 60 % based oven dry weight of raw material). After mat forming, the material was pressed at temperature of 120ºC for 20 minutes. The density of composite was arranged from 0.5, 0.6 and 0.7 g/cm3. Two percent of phenol formaldehyde resin was used to increase the bonding ability of composite material.  The experiment results showed that in general the OS could be used as raw material for production of composite material with medium strength. Modulus of rupture (MOR) could reach 75~120 kg/cm2, while modulus of elasticity (MOE) 5000~7000 kg/cm2. Water absorption of the product was excellent namely below 20 %, and the thickness swelling varied from 8 to 18 %. The leaching test results showed that the leaching of heavy metal was fulfilled the standard